2014
DOI: 10.1080/02699931.2014.881327
|View full text |Cite
|
Sign up to set email alerts
|

Gaze-fixation and pupil dilation in the processing of emotional faces: The role of rumination

Abstract: Sustained attentional processing of negative information plays a significant role in the development and maintenance of depression. The present study examines the relationships between rumination, a relevant factor in information processing in depression, and the attentional mechanisms activated in individuals with different levels of depression severity when attending to emotional information (i.e., sad, angry and happy faces). Behavioural and physiological indicators of sustained processing were assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 56 publications
4
62
1
1
Order By: Relevance
“…To date, few studies have examined relations between cognitive biases and ER processes in depression. Research in (sub)clinically depressed samples has revealed that higher brooding levels are related to negative biases in both attention (Duque, Sanchez, & Vazquez, 2014;Joormann, Dkane, & Gotlib, 2006) and interpretation (Mor, Hertel, Ngo, Shachar, & Redak, 2014). Unfortunately, research linking depression-related cognitive biases to reappraisal is lacking.…”
Section: Toward An Integrative Perspectivementioning
confidence: 99%
“…To date, few studies have examined relations between cognitive biases and ER processes in depression. Research in (sub)clinically depressed samples has revealed that higher brooding levels are related to negative biases in both attention (Duque, Sanchez, & Vazquez, 2014;Joormann, Dkane, & Gotlib, 2006) and interpretation (Mor, Hertel, Ngo, Shachar, & Redak, 2014). Unfortunately, research linking depression-related cognitive biases to reappraisal is lacking.…”
Section: Toward An Integrative Perspectivementioning
confidence: 99%
“…A fixation was defined as a condition in which the eye remained stationary on a predetermined AOI (evaluator, self, or text) for a time interval of 100 ms or more (Wadlinger & Isaacowitz, 2008). In line with recent research, the following dependent variables were calculated (e.g., Duque et al, 2014): (1) Fixation frequency-The number of times a participant directs (redirects) attention to a particular AOI, and is an index of participant's scanning pattern and attentional shifts. (2) Fixation time (or dwell time)-This is the total duration (in ms) a participant has fixated within the boundaries of a particular AOI during a particular social feedback (positive or negative), independent of attentional shifts (e.g., number of fixations).…”
Section: Data Analytic Planmentioning
confidence: 99%
“…We expect depressive brooding, a maladaptive form of emotion regulation, to be inversely correlated to HRV -controlled for the tonic HRV at baselineduring the social feedback (Woody et al, 2014;Pieper et al, 2007). Because rumination has been found to be positively associated with gaze fixation and pupil dilation in the processing of emotional material (e.g., Duque, Sanchez, & Vazquez, 2014), we will also explore the association between depressive brooding and both of these latter physiological indices.…”
mentioning
confidence: 99%
“…Task evokedpupillary responses are a temporally sensitive physiological index that is ideal for assessing emotional reactivity and sustained cognitive processes. [36] and sustained processing also mostly in reaction to negative stimuli [37,38]. These initial adult vs. adolescent findings appear to conflict, since depressed adolescents as a group display diminished sustained pupillary response when compared to healthy youth [34,35].…”
Section: Manuscriptmentioning
confidence: 99%